Risk of developmental delay of children aged between two and 24 months and its association with the quality of family stimulus - Alessandro Fernandes Guimarães; Davi Vilela de Carvalho; Nathália Ádila A. Machado; Regiane Aparecida N. Baptista; Stela Maris A. Lemos (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To analyze the association between neurodevelopment and the family environment resources of children from the coverage area of a Basic Health Unit (BHU) of Belo Horizonte, Brazil, using a tool based on the Integrated Management of Childhood Illness (IMCI) strategy. METHODS: Cross-sectional study with a non-probabilistic sample involving 298 children aged between 2-24 months old, who attended a BHU in 2010. The assessment of child development and family resources made at the BHU lasted, in average, 45 minutes and included two tests - an adaptation of the Handbook for Monitoring Child Development in the Context of IMCI and an adapted version of the Family Environment Resource (FER) inventary. The nonparametric tests of Kruskal-Wallis and Mann-Whitney were used for the statistical analysis. RESULTS: The sample included 291 assessments, with 18.2% of children between 18 and 24 months old, 53.6% male gender, and 91.4% who did not attend day care centers. According to IMCI, 31.7% of the children were in the risk group for developmental delay. The total average score in FER was 38.0 points. Although it has been found an association between the IMCI outcome and the total FER score, all groups had low scores in the family environment assessment. CONCLUSIONS: The data indicate the need for childhood development screening in the primary health care and for early intervention programs aimed at this age group.